Centers of Human Tissue Biomineralization (Calcification) - Pawlikowski, Maciej (Cardiology and Cardiovascular Medicine, 2017)
Biomineralization of tissues includes both mineralization processes that are necessary for the functioning of the organism and those that are harmful for it. This article discusses both types of mineralization, with particular focus on the occurrence of the so-called crystallization centers, i.e. places where the mineralization begins. Primary and secondary crystallization centers are distinguished. Characteristics of developing biomineralization and its consequences are discussed.